Evaluation of Static/Dynamic Cache for Similarity Search Engines - Marin-Caihuan, J; Solar-Gallardo, R (Springer Verlag, 2016)
In large scale search systems, where it is important to achieve a high query throughput, cache strategies are a feasible tool to achieve this goal. A number of efficient cache strategies devised for exact query search in different application domains have been proposed so far. In similarity query search on metric spaces it is necessary to consider additional design requirements devised to produce good quality approximate results from the cache content. In this paper, we propose a Static/Dynamic cache strategy for metric spaces which takes advantage of results of static cache miss operations and their associated distance evaluations for increasing the overall performance of the cache. We present an experimental evaluation of the performance obtained with our strategy for different query selection/replacement strategies. © Springer-Verlag Berlin Heidelberg 2016.